Growth Patterns in the Irish Pyridoxine Nonresponsive Homocystinuria Population and the Influence of Metabolic Control and Protein Intake. (15th November 2017) - Purcell, Orla; Coughlan, Aoife; Grant, Tim; McNulty, Jenny; Clark, Anne; Deverell, Deirdre; Mayne, Philip; Hughes, Joanne; Monavari, Ahmad; Knerr, Ina; Crushell, Ellen
Abstract : A low methionine diet is the mainstay of treatment for pyridoxine nonresponsive homocystinuria (HCU). There are various guidelines for recommended protein intakes for HCU and clinical practice varies. Poor growth has been associated with low cystine levels. This retrospective review of 48 Irish pyridoxine nonresponsive HCU patients assessed weight, height, body mass index (BMI), protein intake, and metabolic control up to 18 years at nine set time points. Patients diagnosed through newborn screening (NBS) were compared to late diagnosed (LD) patients. At 18 years the LD group (n = 12, mean age at diagnosis 5.09 years) were heavier (estimated effect +4.97 Kg, P = 0.0058 ) and taller (estimated effect +7.97 cm P = 0.0204 ) than the NBS group (n = 36 ). There was no difference in growth rate between the groups after 10 years of age. The HCU population were heavier and taller than the general population by one standard deviation with no difference in BMI. There was no association between intermittently low cystine levels and height. Three protein intake guidelines were compared; there was no difference in adult height between those who met the lowest of the guidelines (Genetic Metabolic Dietitians International) and those with a higher protein intake.